2008
DOI: 10.1111/j.1750-3841.2008.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Oregano Essential Oil and MAP to Extend the Shelf Life of Fresh Swordfish: A Comparative Study with Ice Storage

Abstract: The present study evaluated the effect of modified atmosphere packaging (MAP, 5% O(2)/50% CO(2)/45% N(2); treatment M), the addition of oregano oil (0.1%, v/w; treatment AO) as a natural preservative, as well as their combination (treatment MO) on the quality and shelf life extension of fresh Mediterranean swordfish fillets during a refrigerated storage (4 degrees C) period of 18 d. Simultaneously, swordfish fillets were stored under aerobic conditions (control treatment A, 4 degrees C) and on ice (usual comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
8
29
0
1
Order By: Relevance
“…No reductions were found with coatings incorporated 500 ppm of thymol. Similar results have also been reported by Giatrakou et al [25] with slight reductions in counts of TVC, Pseudomonas spp., H 2 S-producing bacteria, and LAB and high reductions in Enterobacteriaceae when treating fresh swordfish with oregano EO. In a similar experiment, Zinoviadou et al [11] treated fresh beef with WPI coatings incorporated with oregano EO and also found significant reductions in counts of TV and LAB during refrigerated storage.…”
Section: Microbiological Changes In Samples Packed Under Air Conditiosupporting
confidence: 80%
See 1 more Smart Citation
“…No reductions were found with coatings incorporated 500 ppm of thymol. Similar results have also been reported by Giatrakou et al [25] with slight reductions in counts of TVC, Pseudomonas spp., H 2 S-producing bacteria, and LAB and high reductions in Enterobacteriaceae when treating fresh swordfish with oregano EO. In a similar experiment, Zinoviadou et al [11] treated fresh beef with WPI coatings incorporated with oregano EO and also found significant reductions in counts of TV and LAB during refrigerated storage.…”
Section: Microbiological Changes In Samples Packed Under Air Conditiosupporting
confidence: 80%
“…When WPI + OR coating was used in combination with MAP, a significant inhibition of TV counts was observed, with >3 log cfu/g reduction at day 12 of storage. Similar results have been reported in previous works [25,29,30]. Despite the final values of C-MAP and WPI-OR-3 samples exceeding the threshold, significant reductions were found during the whole storage period, having higher reductions in C-MAP samples compared with WPI-OR-3 samples.…”
Section: Microbiological Changes In Samples With Low Initial Microbiasupporting
confidence: 79%
“…oregano or thyme essential oil) and vacuum of modified atmosphere packaging on the quality parameters of Mediterranean octopus (Atrea et al 2009), trout (Frangos et al 2010), swordfish (Giatrakou et al 2008;Kykkidou et al 2009) and seabream (Goulas and Kontominas 2007). These studies evaluate the potential use of essential oil compounds and alternative packaging types for the specific species at a single, constant, low temperature (4°C).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, Mahmoud et al (2004) found that dipping carp fillets in carvacrol/thymol solution (1%) both reduced the initial TAMB and extended the shelf life from 4 days to at least 12 days at 5C, according to microbiological results. Besides, Giatrakou et al (2008) reported that the combined use of MAP and oregano oil 0.1% v/wt extended the shelf life of swordfish fillets by 8 days, as determined by sensory and microbiological analysis.…”
Section: Microbiological Analysismentioning
confidence: 98%